Altered IgG autoantibody levels and CD4+ T cell subsets in lupus-prone Nba2 mice lacking the nuclear progesterone receptor. (September 2015) - Wong, Alan H.; Agrawal, Nalini; Hughes, Grant C.
Abstract Important interactions between female reproduction and autoimmunity are suggested by the female-predominance of systemic lupus erythematosus (SLE) and other autoimmune diseases and the amelioration of certain autoimmune diseases during pregnancy. Sexually dimorphic risk of developing SLE involves modulation of genetic risk by environmental factors, sex hormones and non-hormonal factors encoded on the sex chromosomes. In some lupus models, estrogen, via estrogen receptor alpha (ER-α), enhances production of highly pathogenic IgG2a/c autoantibodies (autoAbs). Some studies indicate that treatment with progesterone, a chief female reproductive steroid, can suppress IgG2a/2c autoAb production. Little is known about how endogenous progesterone impacts lupus autoimmunity. To investigate this, we introduced a disruptive progesterone receptor (PR) gene mutation into lupus-prone mice and tracked the development of spontaneous IgG autoAbs. Here, we present evidence that PR can suppress the emergence of class-switched IgG2c autoAbs, suggesting that PR and ER-α counter-regulate a critical step in lupus autoimmunity. PR's control of IgG2c autoAb production correlates with alterations in the relative abundance of splenic T follicular helper (TFH) cells and non-TFH CD4+ T cells, especially regulatory T cells (TREGS). Surprisingly, PR also appears to help to maintain sexually dimorphic abundance of splenic leukocytes, a feature common to many mouse models of SLE. Together our results identify a novel molecular link between female reproduction and lupus autoimmunity. Further investigation into the immunomodulatory functions of PR promises to inform reproductive health care in women and offers mechanistic insight into important immunologic phenomena of pregnancy.